Experiences of specially trained personnel of group education for patients with type 2 diabetes—A lifeworld approach - Andersson, Susanne (Nurs Open, 2019)
AIM: To describe how the group education process for people with type 2 diabetes is experienced by diabetes nurses and dietitians who support the patients’ learning, in a primary care setting. DESIGN: The project took place at two primary care settings in the south of Sweden. METHODS: Data collected from focus‐group interviews and reflection notes were subjected to phenomenological analysis. RESULTS: The specially trained personnel experienced that group education made it possible for the patients to learn through reflection concerning their own and others’ experiences. Furthermore, group education entailed increased knowledge for the trained personnel. When the patients were challenged to make changes in their lives with the illness, the personnel experienced that both patients and personnel supported each other. The study concludes that the trained personnel person‐centred approach, with help of the didactic model, get tools to support patients learning.